(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the need for a socio-educational and pedagogical study of entrepreneurship as a key phenomenon of modern society. The relevance of the topic is due to the increasing role of entrepreneurship in economic, social and cultural development, as well as the need to form new educational approaches that promote the development of entrepreneurial competencies. The genesis of entrepreneurship is analyzed, starting from the historical forms of its manifestation to the modern stage, which made it possible to identify the main factors influencing its development. The purpose of this topic is to ensure the development of educational strategies that integrate entrepreneurial skills, as well as emphasize their role in the sustainable development of society. The research is based on the works of scientists such as J.Schumpeter, who emphasized the role of innovation in entrepreneurship, and M.Weber, who analyzed the cultural and social foundations of this phenomenon. The article focuses on the importance of integrating pedagogical methods aimed at developing students’ critical thinking, creativity, and problem-solving skills. The prospects of creating social and educational platforms for training future entrepreneurs are considered, as well as pedagogical strategies that can contribute to the development of sustainable entrepreneurship in the face of global challenges and changes.